Poniéndonos Lentes de Género para Mejorar la Calidad, la Pertinencia y la Equidad de las Políticas de Educación Profesional y Técnica - Silveira, Sara (Boletim Técnico do Senac, 2006)
This article analyzes gender as a basic element in social relations and in building the identity of men and women, whose inequalities are increased by ethnicity, race, social class, etc. It proposes the gender perspective as a methodology to analyze labor, poverty, vocational training, and technical education. It argues that this approach improves educational technology, and the quality, relevance and equity of vocational training. The article also presents a policy model to enhance employability, citizenship, and equality, approved in several countries. In addition, the model includes its developments: systemic, multidimensional and multiactor approach, curriculum design through gender crossing and education by competences, Guidance and Occupational Project, system of complementary strategies to face inequalities, entrepreneurship learning.